Convenient semihydrogenation of azoarenes to hydrazoarenes using H-2 - Sahoo, Manoj K.; Sivakumar, Ganesan; Jadhav, Sanjay; Shaikh, Samrin; Balaraman, Ekambaram (Organic & Biomolecular Chemistry, 2021)
The high atom-economical and eco-benign nature of hydrogenation reactions make them much more superior to conventional reduction and transfer hydrogenation. Herein, a convenient and highly selective hydrogenation reaction of azoarenes using molecular hydrogen to access diverse hydrazoarenes is reported. The present catalytic method is general and operationally simple, and it operates under exceedingly mild conditions (room temperature and 1 atm of hydrogen pressure). The reusability of catalysts used in this method is also successfully demonstrated.

Recent advances in liquid organic hydrogen carriers: an alcohol-based hydrogen economy - Yadav, Vinita; Sivakumar, Ganesan; Gupta, Virendrakumar; Balaraman, Ekambaram (ACS Catalysis, 2021)
Energy storage and the use of abundantly available feedstock without contributing to the carbon footprint are two significant global challenges. In this regard, the development of high-performance, low-cost, sustainable, and environmentally friendly energy storage and production systems is crucial to fulfill the growing energy demands of the current society. The use of hydrogen will diversify energy sources as it significantly reduces greenhouse gas emissions and environmental pollution during energy conversion. Although the hydrogen economy is quite beneficial, hydrogen storage is still very challenging, and the existing methods suffer from a lot of problems and drawbacks. The conventional liquefaction and compression hydrogen storage technologies are associated with several challenges, including low storage density, boil-off losses, relatively high costs, and safety and transportation concerns. In recent years, liquid organic hydrogen carrier (LOHC) systems have attained a lot of importance as a substitute for the traditional storage methods. Hydrogen storage and transport using LOHCs are based on two-step cycles, such as (i) loading/storage of hydrogen by catalytic hydrogenation of H2-lean compounds and (ii) unloading/releasing hydrogen by dehydrogenating the resulting H2-rich liquids. Since alcohols are widely accessible from various industrial processes or even from biomass-derived precursors, the catalytic acceptorless dehydrogenation of alcohols is an attractive approach for future hydrogen storage applications. Hence, the catalytic dehydrogenation-hydrogenation of alcohols can be used for the development of alcohol-based LOHC systems which are economical, safe, and easy to handle. Further, they are similar to crude oils under ambient conditions and thus are suitable for use in the current energy infrastructure. This Review covers several essential aspects of these developing efficient and abundantly available LOHC systems for efficient hydrogen storage and transport applications. Additionally, reversible LOHC systems based on the catalytic dehydrogenation-hydrogenation of alcohols and their corresponding carbonyl compounds have been discussed.